ASAS NE BIS IN IDEM DALAM KAITANNYA DENGAN PASAL 17 STATUTA ROMA - , MELINDA FERONICA JUNITA MODAMI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
One of the basic principles which adopted in the Rome Statute is tend to \"complementary\". That is, the occurrence of a crime in the International Criminal Court jurisdiction, the subject of a sentence, first must be submitted to the national law of a country where the crime was committed. If the country, in this case, does not want to (unwilling) or can not (unable) judge the subject of such crimes, so the trial of the subject that is performed by the International Criminal Court. This thesis takes the issue of ne bis in idem principle in Article 17 of the Rome Statute related with Article 20 of the Rome Statute. This study is expected to provide a description of the jurisdiction of the International Criminal Court and the principle of ne bis in idem in relating to Article 17 of the Rome Statute in connected with Article 20 of the Rome Statute. The legal research type that was made is normative legal norms research which refers to the legal norms that contained in the legislation. The materials research in this thesis was obtained through the study of literatures and documents. Thus the used instruments is by collecting the laws materials both primary and secondary laws which relates with the problems that was studied. The entire data were analyzed qualitatively. This research produces of âunwillingâ or âunableâ parameters as a consideration to apply ne bis in idem relative principle to have a retrial by the International Criminal Court.